2016
DOI: 10.1002/micr.30020
|View full text |Cite
|
Sign up to set email alerts
|

Free flaps for reconstruction of soft tissue defects in lower extremity: A meta‐analysis on microsurgical outcome and safety

Abstract: Microsurgical reconstruction of soft tissue defects in the lower extremity reconstruction could be regarded safe and reliable. A standardization of report of perioperative parameters and clinical outcomes is needed. © 2016 Wiley Periodicals, Inc. Microsurgery 36:511-524, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0
17

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 55 publications
3
114
0
17
Order By: Relevance
“…This analysis revealed that the gracilis flap was the 3 rd most utilized flap after the anterolateral thigh flap and latissimus dorsi flap 14 . Our failure rate is consistent with this and other published reports 12,14,18 . In a retrospective review of 119 free flaps in 114 patients, Fischer et al reported using the gracilis free flap in only 3 (2.5%) cases.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This analysis revealed that the gracilis flap was the 3 rd most utilized flap after the anterolateral thigh flap and latissimus dorsi flap 14 . Our failure rate is consistent with this and other published reports 12,14,18 . In a retrospective review of 119 free flaps in 114 patients, Fischer et al reported using the gracilis free flap in only 3 (2.5%) cases.…”
Section: Discussionmentioning
confidence: 98%
“…As surgeons became comfortable harvesting the ALT, this flap was found to be reliable and effective in covering open fractures in the lower extremity 911 . While the introduction of locoregional propeller and perforator flaps over the last decade has expanded reconstructive options in the lower extremity, free tissue transfer with the ALT flap has remained the predominant technique for coverage of complex lower extremity defects as it avoids the zone of injury, which often limits the utilization of locoregional flap coverage 1214 . However, despite its popularity, the ALT flap is not without limitations in the coverage of lower extremity defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gir et al believe that pedicled perforator flap use is a safe and reliable procedure for reconstructing soft tissue defects [29]. Xiong et al [30] and Kang et al [31] think that free flap use in foot and ankle reconstruction is safe and reliable due to very robust vascularization and a low risk of infection. However, in our study, Fig 3 and Table 4 indicate that flap type significantly affects the perioperative flap survival rate in the foot and ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions of the endothelial tissue of the vessel and stasis of blood flow are the main factors for thrombosis that may occur during surgery. [7] …”
Section: Introductionmentioning
confidence: 99%